HIV and Respiratory Disease: A Contemporary Perspective - Holt IV, Albert E.; Turenne, Wendy; Slonim, Anthony D. (Current Respiratory Medicine Reviews, 2005)
Human immunodeficiency virus (HIV) infection first manifested itself as Acquired Immune Deficiency Syndrome (AIDS) in the early 1980s when young, previously healthy homosexual men presented with Pneumocystis carinii pneumonia (PCP). Since the discovery of HIV and AIDS, many different respiratory infections (common, uncommon and opportunistic), as well as different malignancies such as Kaposi's sarcoma, and destructive lung processes, such as emphysema have been shown to occur more commonly in the setting of HIV. Alterations in the CD4+/CD8+ lymphocyte composition and changes in the function of B cells compromise host defenses and predispose an HIV infected individual to respiratory infections. Highly Active Antiretroviral Therapy (HAART) has dramatically altered the course of HIV infection through suppression of viral replication, a reconstitution of CD4+ cells, and the resultant decrease in opportunistic infections, including PCP. This manuscript provides a contemporary review of the respiratory diseases of patients with HIV.
Keywords: cytomegalovirus infections